Kalang, Tinjauan Historis-Antropologis - Bambang Sulistyanto (Balai Arkeologi Yogyakarta, 1994)
The terms of “kalang” substantially mentioned in Old Javanese inscriptions. It’s meaning oftenly associated with professions in the timber producing or carpentry. It’s definition drawn from the existence of